2010
DOI: 10.1016/j.devcel.2009.12.017
|View full text |Cite
|
Sign up to set email alerts
|

ATRX Partners with Cohesin and MeCP2 and Contributes to Developmental Silencing of Imprinted Genes in the Brain

Abstract: Human developmental disorders caused by chromatin dysfunction often display overlapping clinical manifestations, such as cognitive deficits, but the underlying molecular links are poorly defined. Here, we show that ATRX, MeCP2, and cohesin, chromatin regulators implicated in ATR-X, RTT, and CdLS syndromes, respectively, interact in the brain and colocalize at the H19 imprinting control region (ICR) with preferential binding on the maternal allele. Importantly, we show that ATRX loss of function alters enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 60 publications
(78 reference statements)
2
137
0
Order By: Relevance
“…Gabory et al (2009) also demonstrated that such regulation via H19 apparently did not operate in the placenta, which implies a notable degree of tissue and stage specificity of imprinted-gene network dynamics. Most recently, loss of expression of the ATRX gene in mice has been shown to cause altered postnatal expression of a suite of imprinted genes including Igf2, H19, Dlk1, Zac1, and Peg1, as well as the Rett-syndrome gene MeCP2, suggesting a role for ATRX in transregulation of the imprinted-gene network (Kernohan et al 2010) and corroborating effects of MeCP2 expression in the regulation of imprinted genes (Miyano et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Gabory et al (2009) also demonstrated that such regulation via H19 apparently did not operate in the placenta, which implies a notable degree of tissue and stage specificity of imprinted-gene network dynamics. Most recently, loss of expression of the ATRX gene in mice has been shown to cause altered postnatal expression of a suite of imprinted genes including Igf2, H19, Dlk1, Zac1, and Peg1, as well as the Rett-syndrome gene MeCP2, suggesting a role for ATRX in transregulation of the imprinted-gene network (Kernohan et al 2010) and corroborating effects of MeCP2 expression in the regulation of imprinted genes (Miyano et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Atrx has been shown to be critical for mouse extraembryonic trophoblast formation and subsequent embryo survival 9.5 d postcoitus and is also involved in developmental silencing of imprinted genes [Kernohan et al 2010] and may prove to be a non-invasive marker of an oocyte's developmental competence. Markers in the cumulus cells that surround the oocyte are of particular interest allowing for a non-invasive method of detecting oocyte quality without destroying the oocyte in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mecp2 directly regulates a large cluster of mi-RNAs within the Dlk1-Gtl2 imprinting domain. Kernohan et al (2010) pointed out that the methylation region close to the Gtl2 promoter is associated with X-linked a thalassemia/mental retardation syndrome (168 patients reported in the European Community), suggesting a role for Mecp2 in the transcriptional control of this region.…”
Section: Rare Diseases May Share Common Pathophysiological Mechanismsmentioning
confidence: 99%